DETERMINASI DALAM PENDETEKSIAN KECURANGAN - Surtikanti, Surtikanti; Supriyanto, Joko; Suryana, Nanang; Azbi, Raihan Muhammad (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
This study aims to find out how the factors possessed by an auditor are professional skepticism, independence and competence in fraud detection. The research methods used in this study are descriptive and verifiable methods with a quantitative approach. The population in this study are 139 auditors who works in the 13 public accounting firms in Bandung. The sample used in this study amounted to 40 auditors with sample collecting techniques using the non-probability sampling technique with the method used purposive sampling which means the sampling technique is based on certain criteria. Data analysis methods in the study use linear regression, determinations, corelation coefficiencies, and hypothesis testing with the help of SPSS 23.0. Results have shown that professional skepticism, independence and competence have a positive and significant impact on fraud detection. Keywords: Professional Skepticism, Independence, Competence, Fraud Detection